Rationalization of the use of water in vegetable and nursery crops - Colombo A.; Rizzi A.; Tosca A.; D'Angelo G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The rational use of water in agriculture is an urgent aim, since there is a lack of water in many places in the world. The evolution of more efficient irrigation systems in vegetable and nursery crops growing has been remarkable. There has been a change from gravity irrigation systems, such as flowing irrigation, with rather low efficiency index, to pressure irrigation systems, such as subirrigation, overhead and localized irrigation. In order to exploit the sub-irrigation advantages new cultivation systems are developed. These new systems are based on the sub-irrigation, adjusted by the use of special mats with high water retention capacity. These irrigation systems guarantee the retention of water and nutrients which, in the older systems, have been lost during irrigation.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)